2017
DOI: 10.1038/s41514-016-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors that promote the differentiation of human pluripotent stem cells into lacrimal gland epithelium-like cells

Abstract: Dry eye disease is the most prevalent pathological condition in aging eyes. One potential therapeutic strategy is the transplantation of lacrimal glands, generated in vitro from pluripotent stem cells such as human embryonic stem cells, into patients. One of the preceding requirements is a method to differentiate human embryonic stem cells into lacrimal gland epithelium cells. As the first step for this approach, this study aims to identify a set of transcription factors whose overexpression can promote the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Animal models for efficient tissue damage have been reported for investigation on mechanism of inflammation, regenerative potential of organs, and isolation of stem/progenitor cells from the target organs [ 8 , 25 29 ]. Previous studies have shown that a partial radiation to salivary glands in mice leads to proliferation of cells, which have an ability to form salispheres for cell injection therapy to restore the salivary gland functions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models for efficient tissue damage have been reported for investigation on mechanism of inflammation, regenerative potential of organs, and isolation of stem/progenitor cells from the target organs [ 8 , 25 29 ]. Previous studies have shown that a partial radiation to salivary glands in mice leads to proliferation of cells, which have an ability to form salispheres for cell injection therapy to restore the salivary gland functions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Overexpression of tissue-specific transcription factors in human pluripotent stem cells can successfully induce the LG epithelial cell phenotype. 41 Using such induced epithelial and mesenchymal cells, small functional LGs may be generated via epithelial-mesenchymal interactions ex vivo. These generated LGs might be similar to an accessory LG rather than the main LG, but when transplanted, may work as functional LGs.…”
Section: Possibility Of Lacrimal Functional Restoration By Regeneratimentioning
confidence: 99%
“…94,95 Recently, a whole gene expression analysis based on microarray technology identified a subset of transcription factors (PAX6, FOXC1, SIX1, and SIX2) that are specifically and highly expressed in the ED16.5 mouse lacrimal gland epithelium compared with developmentally related organs such as the mature lacrimal glands, the mature/embryonic harderian glands and the embryonic ocular surface epithelium. 96 These transcription factors have been implicated as part of a set of core transcription factors that define the lacrimal gland epithelial cell lineage. Specifically, the overexpression of PAX6, FOXC1, and SIX1 using transcription factor-coded synthetic mRNAs in human ESCs resulted in the differentiation of cells toward the lacrimal gland epithelial cell like phenotype accompanied by expression of a part of lacrimal gland development markers, including the immature lacrimal gland epithelial marker KRT15, the branching morphogenesis marker BARX2, and the tear secretion related markers AQP5 and lactoferrin.…”
Section: Cutting-edge Strategies To Regenerate the Lacrimal Glands Inmentioning
confidence: 99%